Epidemiological aspects of mortality due to diseases of the circulatory system in Foz do Iguaçu between the years 2010 and 2022 (Research, Society and Development, 2024)
Objective: To investigate the association of health and sociodemographic changes with mortality due to circulatory system diseases (CSD) in the municipality of Foz do Iguaçu between 2010 and 2022. Method: Descriptive time series study, referring to the period from 2010 to 2022, based on secondary data, with the municipality of Foz Do Iguaçu as the unit of analysis. The Mortality Information System available in the “TABNET” application and the database of the Brazilian Institute of Geography and Statistics were used. The variables studied were: sex, race, place of occurrence, age, total number of cases, marital status and education. The following codes from the 10th international classification of diseases (ICD-10) were used in TABNET: 066-072, in order to filter the total number of cardiovascular diseases. Data were described by percentage calculation and statistical analysis in an electronic spreadsheet. Results: Total of 4.763 deaths from diseases of the cardiovascular system were recorded in the municipality of Foz do Iguaçu, and 268.280 in Paraná, between the years 2010 and 2022. Furthermore, 77.98% of deaths occurred in individuals over 60 years of age with a preponderance of males, white, with low education and married. Conclusion: An age predominance was observed in the pattern of mortality and an increase in incidence by CSD in the municipality of Foz do Iguaçu.